The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1007/s10750-005-4452-3
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Responses of Planktonic Crustaceans to Fish Predation by Shifts in Depth Selection and Size at Maturity

Abstract: We investigated the behaviour and life histories of large zooplankton in the Esch-sur-Suˆre reservoir (Luxembourg). We found that the decrease in size at maturity, as well as diurnal refuge in deep waters, were the adaptive responses (concurrently or alternatively) adopted by large zooplankters to cope with the increasing predation risk throughout the summer. Daphnia galeata initiated a more severe trade-off to cope with high summer predation relative to other cladoceran species. Diaphanosoma brachyurum and Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Despite Eudiaptomus gracilis is often presented as a herbivorous species, its clearance rates on protozoa are similar to those of cladocerans such as Bosmina longirostris or Daphnia hyalina (Ju¨rgens et al, 1996;Jack & Gilbert, 1997). Contrary to what has happened in May, metazooplankton is not able to control protozoa and phytoplankton because it is itself controlled by juvenile fishes that move out into the pelagic zone at this time (Thys & Hoffmann, 2005). Reduced grazing pressure also beneficiated to phytoplankton whose biomass reached maximum values in mid-July.…”
Section: Seasonal Patterns Of Protozoa Developmentmentioning
confidence: 94%
“…Despite Eudiaptomus gracilis is often presented as a herbivorous species, its clearance rates on protozoa are similar to those of cladocerans such as Bosmina longirostris or Daphnia hyalina (Ju¨rgens et al, 1996;Jack & Gilbert, 1997). Contrary to what has happened in May, metazooplankton is not able to control protozoa and phytoplankton because it is itself controlled by juvenile fishes that move out into the pelagic zone at this time (Thys & Hoffmann, 2005). Reduced grazing pressure also beneficiated to phytoplankton whose biomass reached maximum values in mid-July.…”
Section: Seasonal Patterns Of Protozoa Developmentmentioning
confidence: 94%
“…However, we did not observe this migration pattern in this study, and most D. brachyurum individuals remained in the bottom layer during the night in reservoirs with D max >6 m. Adamczuk (2009) also reported that D. brachyurum did not perform migrations pattern. They seem less susceptible to fish predation as indicated by the low alteration of their vertical distribution (Thys and Hoffmann, 2005). Therefore, D. …”
Section: Discussionmentioning
confidence: 99%
“…Parental care behavior increases the competitiveness of peacock bass (Latini & Petrere, 2004), and, along with feeding plasticity could be important for successful colonization of lentic habitat. The lentic characteristics of reservoirs cause considerable water transparency and facilitate predation Thys & Hoffmann, 2005) by diurnal piscivores like the peacock bass (Novaes et al, 2004). Furthermore, abundant prey during the colonization phase (Agostinho et al, 1999) may also aid in the success of this species.…”
Section: Discussionmentioning
confidence: 99%